Muslim feminism: A systematic literature review and bibliometric analysis - Wahyuningsih, Wahyuningsih (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Islamic feminism has emerged as a critical epistemological framework that integrates gender justice with Islamic values, necessitating systematic exploration due to its fragmented and context-dependent nature. This study aims to map the development of Islamic feminism through a Systematic Literature Review using the PRISMA framework to identify theoretical trends and gaps within the field. While it promotes women's agency through contextual, faith-based strategies, its acceptance remains contested due to political resistance and limited intersectional solidarity. Methods: This study employs a Systematic Literature Review (SLR) approach based on the PRISMA framework to evaluate literature on Islamic feminism as an epistemological approach in Islamic studies. Articles were collected from the Scopus database, limited to English-language publications from 1990 to 2025. Bibliometric analysis was conducted using VOSviewer to map keyword trends, author networks, and citation relationships among the literature. Findings: The findings reveal a significant development in the discourse of Islamic feminism, particularly in the Global North and in Muslim-majority countries such as Iran and Indonesia. The main emerging themes include the reinterpretation of religious texts and critiques of patriarchal social structures within Muslim societies. However, the integration of hermeneutical approaches and social critique into a cohesive epistemological framework remains suboptimal. Conclusion: This study concludes that Muslim feminism is a dynamic and expanding discourse that emphasizes culturally grounded social experiences and epistemological reform in Islamic thought. Its global and transnational character highlights its role as both a theoretical and practical framework for advancing justice, equality, and contextual scholarship in contemporary Islamic studies. Novelty/Originality of this article: Ultimately, this review provides a comprehensive analysis that contributes to the academic development of Islamic feminism and informs educational and policy-oriented practices aligned with human rights and social justice.